1986
DOI: 10.1271/bbb1961.50.2585
|View full text |Cite
|
Sign up to set email alerts
|

Substrate binding sites of Leuconostoc dextransucrase evaluated by inhibition kinetics.

Abstract: Graphical analysis of inhibition kinetics for dextransucrase from Leuconostoc mesenteroides was done with typical inhibitors, competitive and noncompetitive. Based on the plots of Yonetani-Theorell and Semenza-Balthazar, mutual competition between the pairs of inhibitors of identical kinetic type was observed, while combination of competitive and noncompetitive inhibitors gave no significant mutual interactions. By the procedure ofNitta et aL, binding sites for competitive and noncompetitive inhibitors were sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Some recent studies based on cloning of glucansucrases encoding gene in addition to the structure-function relationship studies showed two functional domains: a core region involved in sucrose binding and a C-terminal domain involved in glucan-binding [9]. These recent works confirm that glucan-biding site is separated from sucrose biding site as previously suggested [10][11][12].…”
Section: Discussionsupporting
confidence: 69%
“…Some recent studies based on cloning of glucansucrases encoding gene in addition to the structure-function relationship studies showed two functional domains: a core region involved in sucrose binding and a C-terminal domain involved in glucan-binding [9]. These recent works confirm that glucan-biding site is separated from sucrose biding site as previously suggested [10][11][12].…”
Section: Discussionsupporting
confidence: 69%
“…It has been proposed that glucan is bound to the enzyme through non‐covalent links [38]. More recently, results coming from inhibition kinetic studies using various agents suggested that the glucan binding site was separated from the sucrose binding site [47–51]. This hypothesis has also been confirmed by the identification of glucansucrase sequences and by structure–function relationship studies (see ).…”
Section: Mechanism Of Glucansucrase Actionmentioning
confidence: 89%
“…The necessity of a primer was first accepted in relation to glycogen synthesis mechanism studies carried out at the same period [43]. This hypothesis has been supported by the fact that addition of exogenous glucan has an activating effect on glucan synthesis [50, 52, 53]. However, glucansucrases are active enzymes in the absence of any exogenous primer.…”
Section: Mechanism Of Glucansucrase Actionmentioning
confidence: 99%
“…The precise mechanism of glucansucrases is still not fully understood (Monchois et al, 1999;Robyt, 1995). In the literature, elongation of the glucan chains has been proposed to occur at the non-reducing end (Kobayashi et al, 1986;Mooser et al, 1985) or at the reducing end (Ebert and Schenk, 1968;Robyt et al, 1974).…”
Section: Introductionmentioning
confidence: 99%